Factors associated with nutritional status, knowledge and attitudes among tuberculosis patients receiving treatment in Ghana: A cross-sectional study in the Tema Metropolis. - Prince Kubi Appiah (Public Library of Science (PLoS), 2021)
Background Nutritional deficiencies are generally associated with increased risk and severity of tuberculosis. This study investigated the nutritional status, knowledge, and attitudes of tuberculosis (TB) patients receiving treatment in the Tema Metropolis. Method A cross-sectional design was used to collect data on the nutritional knowledge, attitude, and status of TB patients. Nutritional status was analysed using World Health Organization's formula for body mass index. Pearson's chi-square and logistic regression models were used to assess associations between predictor and outcome variables. All statistical analyses were considered significant at p-values < 0.05. Result The prevalence of malnutrition among TB patients was 39.7%, 14.4%, and 4.8% for underweight, overweight, and obesity respectively. There was a high (61.0%) knowledge of nutrition among the patients. Also, 65.8% had good attitude towards nutrition. There were significant associations between normal nutritional status and age of the TB patients (p = 0.041), highest educational level attained (p = 0.036), employment status (p = 0.019), status of alcohol intake (p = 0.031), number of months on TB treatment (p = 0.021), and attitude towards nutrition (p = 0.028). Conclusion There was a reasonable nutrition-related knowledge and attitude towards nutrition among the TB patients. However, that did not reflect on their nutritional status. We recommend continuing education on smoking cessation, avoidance of harmful use of alcohol, and the establishment of food aid and other livelihood intervention programs for TB patients.